128-Slice CT in the Assessment of Saphenous Vein Grafts at Redo Coronary Artery Bypass Grafting - Strecker, Thomas; Kondruweit, Markus; Weyand, Michael; Ropers, Dieter (Journal of cardiac surgery, 2009)
Reoperations for coronary artery bypass grafting (CABG) are increasing. The general rule of replacing all saphenous vein grafts older than five years of age at the time of reoperation is still an object of discussion. We report here the clinical usefulness of the new 128‐slice computed tomographic scan to detect or rule out coronary artery disease in a 79‐year‐old patient who had undergone CABG 22 years before.